Onoceranoid Triterpenes of Lansium domesticum Corr. cv. Kokossan and Their Cytotoxicity against MCF-7 Breast Cancer Cells - Mayanti, Tri; Azahra, Salwa Alya; Syafriadi, Tasya Putri; Nurlelasari, Nurlelasari; Maharani, Rani; Julaeha, Euis; Supratman, Unang; Sinaga, Siska Elisahbet; Ekawardhani, Savira; Fajriah, Sofa (Trends in Sciences, 2024)
The onoceranoid triterpenes isolated from the kokossan fruit peels were studied in vitro using MCF-7 breast cancer cells. Three onoceranoids, namely 8,14-secogammacera-8(26),14-dien-3,21-diol (1), 3β-hydroxyonocera-8(26),14-dien-21-one (2) and α,γ-onoceradienedione (3), were obtained from the ethyl acetate extract of kokossan fruit peels. Compounds 1 - 3 were obtained for the first time from this cultivar. Several spectroscopic methods, including IR, HR-TOFMS and 1,2 D-NMR, were used to determine the chemical structures of compounds (1 - 3), and the results were compared to spectrum data that had previously been published. Additionally, the activity of compounds 1 - 3 was assessed in vitro using MCF-7 cells. With an IC50 value of 17.11 µg/mL, compound 2 demonstrated the highest activity in the activity test findings, followed by compounds 3 and 1, with IC50 values of 19.66 and > 150 µg/mL, respectively. When compared to cisplatin as a positive control, compounds 2 and 3 showed considerable potency, while compound 1 showed no activity. Compounds 2 and 3 were the most promising candidates for the anticancer drug; nevertheless, more testing is necessary to ascertain their biological mechanism for future research. HIGHLIGHTS Lansium domesticum is a tropical fruit-bearing tree with significant economic and medicinal value. It has been traditionally used for various ailments, including fever, dysentery, and malaria, due to its rich phytochemical composition. Kokossan is a cultivar of Lansium domesticum that has not been widely studied for its onoseronoid content, especially in the skin of the fruit. 8,14-sekogammacera-8(26),14-dien-3,21-diol (1), 3β-hydroxyonocera-8(26),14-dien-21-one (2), and α,γ-onoceradienedione (3). For the first time, these two compounds (1 and 2) were separated from this genus; earlier, this compound was the outcome of the reduction (synthesis) of compound 3. 3β-hydroxyonocera-8(26),14-dien-21-one exhibited the highest IC50 value compared to α,γ-onoceradienedione and . 8,14-sekogammacera-8(26),14-dien-3,21-diol. Compounds 2 and 3 demonstrated potential as anticancer agents, with activity comparable to the standard drug cisplatin. This provides insight that onoceranoids have the potential as chemopreventive agents to treat breast cancer. GRAPHICAL ABSTRACT